Multisource noninvasive genetics of brown bears (Ursus arctos) in Greece reveals a highly structured population and a new matrilineal contact zone in southern Europe. Issue 11 (2nd May 2021) - Pylidis, Charilaos; Anijalg, Peeter; Saarma, Urmas; Dawson, Deborah A.; Karaiskou, Nikoleta; Butlin, Roger; Mertzanis, Yorgos; Giannakopoulos, Alexios; Iliopoulos, Yorgos; Krupa, Andrew; Burke, Terence A.
Abstract: In human‐dominated landscapes, connectivity is crucial for maintaining demographically stable mammalian populations. Here, we provide a comprehensive noninvasive genetic study for the brown bear population in the Hellenic Peninsula. We analyze its population structuring and connectivity, estimate its population size throughout its distribution, and describe its phylogeography in detail for the first time. Our results, based on 150 multilocus genotypes and on 244‐bp sequences of the mtDNA control region, show the population is comprised by three highly differentiated genetic clusters, consistent with geographical populations of Pindos, Peristeri, and Rhodope. By detecting two male bears with Rhodopean ancestry in the western demes, we provide strong evidence for the ongoing genetic connectivity of the geographically fragmented eastern and western distributions, which suggests connectivity of the larger East Balkan and Pindos‐Dinara populations. Total effective population size ( N e ) was estimated to be 199 individuals, and total combined population size ( N C ) was 499, with each cluster showing a relatively high level of genetic variability, suggesting that migration has been sufficient to counteract genetic erosion. The mtNDA results were congruent with the microsatellite data, and the three genetic clusters were matched predominantly with an equal number of mtDNA haplotypes that belong to the brown bear Western mitochondrial lineage (Clade 1), with two haplotypes being globally new and endemic. The detection of a fourth haplotype that belongs to the Eastern lineage (Clade 3a1) in three bears from the western distribution places the southernmost secondary contact zone between the Eastern and Western lineages in Greece and generates new hypotheses about postglacial maxima migration routes. This work indicates that the genetic composition and diversity of Europe's low‐latitude fringe population are the outcome of ancient and historical events and highlight its importance for the connectivity and long‐term persistence of the species in the Balkans. Abstract : Using microsatellites and mtDNA, we reveal the genetic structure, diversity, population size of the brown bear in Greece, and its detailed phylogeography for the first time, revealing a new matrilinear contact zone